Las vías de hecho como generadoras del choque de trenes en la jurisprudencia constitucional (1992-2008) - Gómez García, Carlos Fernando (2023)
The conflict of constitutional jurisd iction among high courts in Colombia has come to be called a “train wreck”, and it has been studied in depth by the Colombian Constitutional Court. This article tries to show how the Court has treated this subject, and how its stance has evolved over a ser ies of opinions.